Homogeneity and heterogeneity in lexical stress placement among Ugandan speakers of English as an L2 - Monica Adokorach; Bebwa Isingoma (ExELL (Explorations in English Language and Linguistics), 2025)
The study delineates divergences that set apart the Ugandan accent from RP with respect to primary lexical stress placement, as well as divergences that evince variability among Ugandans. For example, differences from RP were (almost) homogenously observed in the words effect, cassava, agreement, arrest, alarm, with stress placed on the first syllable of all these nouns, while inter-speaker variability was substantially observed in words such as bursar, further, with some speakers placing stress on both syllables of the words, while others had the stress on the first syllable only. Analogy and underlying substrate influence account for the divergences, with substrate influence considered along the lines of what Wells (1982) refers to as ‘lexical distribution.